A picture of regret: An empirical investigation of post-Brexit referendum survey data. (February 2022) - Collins, Alan; Cox, Adam; Torrisi, Gianpiero
Whilst the properties of decision regret have been widely explored in experimental and game theoretic studies, the empirical features of regret from large-scale 'binary decision' national events in practice have garnered less scrutiny. This study is an empirical investigation of novel survey data reporting 'Brexit' voting choices and expressions of a desire to change voting choices post-referendum. We investigate if Leave voters are more or less likely to express a change to their binary referendum vote choice than those who voted Remain or abstained and then identify the particular characteristics of those who regret their vote choice. A large-scale pan-European survey is used to capture citizens' perceptions of the European Union containing 17, 147 interviews of adults from 15 EU member states. Using responses from UK citizens ( n = 1500), focus is directed to the vote choice for the 'Brexit' referendum and the corresponding choice if the referendum were held 'today'. Probit regression estimation identifies the key differences in the characteristics of those who expressed regret by indicating a desire to change voting choices. Results show that knowledge of EU funding policies, permanence of residential location, population size of the local area, educational attainment, employment status and income are key drivers for regretting the referendum voting decision.